Assessment of Antimicrobic, Antivirotic and Cytotoxic Potential of Alginate Beads Cross-Linked by Bivalent Ions for Vaginal Administration - Pavelková, Miroslava; Vysloužil, Jakub; Kubová, Kateřina; Pavloková, Sylvie; Molinková, Dobromila; Celer, Vladimír; Pechová, Alena; Mašek, Josef; Vetchý, David (Pharmaceutics, 2021)
Antimicrobial agent abuse poses a serious threat for future pharmacotherapy, including vaginal administration. The solution can be found in simple polymeric systems with inherent antimicrobial properties without the need to incorporate drugs, for instance alginate beads cross-linked by bivalent ions. The main goal of the presented study was to provide improvement on the well-documented cytotoxicity of Cu2+ cross-linked alginate. Alginate beads were prepared by external ionotropic gelation by cross-linking with Cu2+, Ca2+ and Zn2+ ions, separately and in mixtures. Morphological properties, swelling capacity, ion release and efficacy against the most common vaginal pathogens (C. albicans, E. coli, E. faecalis and virus strain-human herpesvirus type 1) were evaluated. The prepared particles (particle size 1455.68 ± 18.71-1756.31 ± 16.58 µm) had very good sphericity (0.86 ± 0.04-0.97 ± 0.06). In mixture samples, Cu2+ hampered second ion loading, and was also released incompletely (18.75-44.8%) compared to the single ion Cu2+ sample (71.4%). Efficacy against the selected pathogens was confirmed in almost all samples. Although anticipating otherwise, ion mixture samples did not show betterment over a Cu2+ cross-linked sample in cytotoxicity-pathogen efficacy relation. However, the desired improvement was found in a single ion Zn2+ sample whose minimal inhibition concentrations against the pathogens (0.6-6.12 mM) were close to, or in the same mathematical order as, its toxic concentration of 50 (1.891 mM). In summary, these findings combined with alginate's biocompatibility and biodegradability give the combination solid potential in antimicrobial use.
Keywords: antiviral activity; antimicrobial activity; alginate; cross-linking; cytotoxicity; ionic gelation; bivalent ions